Hydrophobic aluminum nitride powder and method for producing the same

CN116438237BActive Publication Date: 2025-01-28TOKUYAMA CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202180075091.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-12-15
Filing Date
2021-12-13
Publication Date
2025-01-28
Estimated Expiration
2041-12-13

AI Technical Summary

Technical Problem

The existing aluminum nitride powder is prone to hydrolysis when in contact with water, resulting in insufficient water resistance when used in high humidity environments, limiting its application in electronic materials.

Method used

Through the use of sirrius compounds for surface treatment, aluminum nitride powder is given a certain degree of hydrophobicity, while maintaining a moderate affinity with resin at the same time, which effectively suppress hydrolysis reaction.

Benefits of technology

The hydrolysis of aluminum nitride powder in the resin is realized, and its water resistance in high humidity environment is enhanced, and it is suitable for high -performance electronic materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004213271970000321
    Figure BDA0004213271970000321
  • Figure BDA0004213271970000331
    Figure BDA0004213271970000331
  • Figure BDA0004213271970000341
    Figure BDA0004213271970000341
Patent Text Reader

Abstract

The hydrophobic aluminum nitride powder of the present invention is characterized in that it is a hydrophobic aluminum nitride powder having a hydrophobicity of 1 to 45, the carbon content derived from a hydrophobic agent is in the range of 0.1 to 0.5 mass %, and the hydrophobic agent is a silane compound.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a novel hydrophobic aluminum nitride powder, and more specifically, to an aluminum nitride powder to which hydrophobicity is imparted by surface treatment using a silane compound. Background Art

[0002] In recent years, due to the demand for miniaturization and high performance of electronic components, the high integration of semiconductor devices has been promoted. Along with this, the amount of heat dissipation materials used to effectively dissipate the heat generated by the devices has increased. In addition, the heat dissipation performance is required to be further improved. In order to dissipate the heat generated by semiconductor devices to radiators, housings, etc., heat dissipation materials are arranged in various paths, and the materials and forms of heat dissipation materials are also varied. Among them, heat dissipation resin materials filled with filler powders with high thermal conductivity have various materials and forms, so the demand in the market is rising.

[0003] Representative fillers having high thermal conductivity include aluminum oxide, aluminum nitride, boron nitride, zinc oxide, magnesium oxide, etc. Also, heat sinks, semiconductor encapsulation materials, heat dissipation greases, heat dissipation adhesives, etc. are known as heat dissipation resin materials blended with these fillers.

[0004] Among the aforementioned fillers, aluminum nitride (AlN) powder has a particularly high thermal conductivity, which is several dozen times higher than silicon dioxide and five times higher than aluminum oxide, and therefore is highly anticipated as a heat dissipation filler. In addition, high insulation is required for electronic device applications, and therefore, as a filler to be filled into resin, a filler that is chemically stable and does not release ionic impurities is sought.

[0005] However, although AlN powder has high insulation properties, it is easily hydrolyzed to generate ammonium ions when in contact with water, and therefore, the use of molded bodies composed of resin compositions filled with AlN powder in applications requiring high insulation properties is limited. That is, when in contact with water or in a high humidity atmosphere, water will penetrate into the molded body (AlN-containing resin) and come into contact with AlN in the molded body, thereby causing hydrolysis.

[0006] Patent document 1 proposes AlN powder that is surface treated with orthophosphoric acid to impart water resistance. However, phosphorus compounds have concerns about the dissolution of phosphate ions, which needs to be avoided in electronic materials requiring high insulation. In addition, epoxy resins are mostly mixed with alkaline curing agents such as amines. Therefore, if AlN powder surface treated with orthophosphoric acid is mixed with epoxy resin, the alkaline curing agent will react with the phosphate group, resulting in the loss of the film of aluminum phosphate compound formed on the surface of the AlN particles, resulting in the problem of deterioration of the water resistance of AlN present in the epoxy resin.

[0007] In addition, Patent Document 2 proposes a solution to improve moisture resistance by forming a silicon oxide coating on the surface of AlN. That is, by forming a silicon oxide coating on the surface, hydrolysis caused by contact between AlN and water can be suppressed. However, silicon oxide has low thermal conductivity, which not only reduces the thermal conductivity of AlN, but also easily generates aggregated particles in the surface treatment process of coating silicon oxide, which may deteriorate the filling property of the resin.

[0008] Furthermore, Patent Document 3 shows that the water resistance at room temperature is improved by surface treating the AlN powder with a hydrophobizing agent composed of an organosilane having a long-chain alkyl group of 9 to 15 carbon atoms. However, although the AlN powder treated with a hydrophobizing agent having a strong hydrophobic group with a long-chain alkyl chain shows extremely high hydrophobicity, the water resistance in the resin is insufficient. That is, when the powder is filled in the resin, the hydrolysis of the AlN powder caused by the penetration of water in the resin (i.e., hydrolysis in the resin) cannot be fully prevented, and there is room for further improvement.

[0009] Furthermore, Patent Document 4 proposes aluminum nitride powder subjected to surface treatment with alkoxy-modified silicone, and Patent Document 5 proposes ceramic powder coated with an organic compound which is a reaction product with a silane coupling agent or a titanium coupling agent.

[0010] However, although the aluminum nitride powder surface-treated with alkoxy-modified silicone in Patent Document 4 has high water resistance (hydrolysis resistance) in the powder state, similarly to Patent Document 3, its water resistance in the state of being blended in a resin is insufficient and needs to be improved.

[0011] Furthermore, when the surface treatment technique of Patent Document 5 is applied to aluminum nitride powder, the water resistance of the aluminum nitride powder in a state of being mixed with a resin is also insufficient.

[0012] The above-mentioned problem becomes a problem particularly in aluminum nitride powder composed of particles having a relatively small particle size.

[0013] Prior art literature

[0014] Patent Literature

[0015] Patent Document 1: Japanese Patent Application Laid-Open No. 9-202608

[0016] Patent Document 2: Japanese Patent Application Publication No. 2004-83334

[0017] Patent Document 3: Japanese Patent Application Publication No. 2000-129160

[0018] Patent Document 4: Japanese Patent Application Publication No. 2005-104765

[0019] Patent Document 5: Japanese Patent Application Laid-Open No. 60-123561 Summary of the invention

[0020] Problem that the invention aims to solve

[0021] Therefore, an object of the present invention is to provide a hydrophobic aluminum nitride powder which, when filled in a resin, can highly suppress the hydrolysis of the aluminum nitride caused by contact with water infiltrating into the resin and can exhibit high water resistance.

[0022] Solutions for solving problems

[0023] The present inventors have repeatedly conducted in-depth research to achieve the above-mentioned purpose, and the following insights have been obtained as a result: when aluminum nitride (AlN) powder is filled into a resin, a gap will be generated at the interface between the particles of the AlN powder and the resin, and the water immersed in the resin will accumulate in the above-mentioned gap, thereby causing the hydrolysis of the AlN caused by contact with the water that penetrates into the resin to proceed rapidly. In addition, the following insights have been obtained: if the AlN powder is excessively hydrophobized with a hydrophobizing agent in order to improve water resistance, the affinity with the resin is reduced, which in turn promotes the occurrence of the aforementioned gap, and the hydrolysis of the AlN is further carried out. Based on these insights, further repeated research has been conducted, and it has been found that the AlN powder that has been given a certain degree of hydrophobicity by surface treatment with a hydrophobizing agent will simultaneously show hydrophobicity and a moderate affinity with the resin, and can effectively suppress the hydrolysis caused by the water that penetrates into the resin, and the present invention has been completed.

[0024] That is, according to the present invention, there is provided a hydrophobic aluminum nitride powder, characterized in that the hydrophobic aluminum nitride powder has a hydrophobization degree of 1 to 45.

[0025] The carbon content derived from the hydrophobizing agent is in the range of 0.1 to 0.5 mass %, and the hydrophobizing agent is a silane compound.

[0026] The hydrophobic aluminum nitride powder of the present invention can be preferably used in the following forms.

[0027] (1) The molecular weight of the silane compound is 400 or less.

[0028] (2) The hydrophobization degree is in the range of 1 to 30.

[0029] (3) In the particle size distribution measured by a laser diffraction scattering type particle size distribution analyzer using an ethanol solvent, the particle size D at which the cumulative volume is 50% is 50 0.5~20μm.

[0030] (4) the decomposition rate of the aluminum nitride measured after immersing the following test body in 50 g of ion exchange water at 120° C. for 90 hours (hereinafter sometimes referred to as the basic hydrolysis rate within the resin) is 25% or less,

[0031] The test body is a 10 mm φ×1.2 mm thick molded body formed from a resin composition obtained by blending 25 parts by mass of a hydrophobic aluminum nitride powder with respect to 100 parts by mass of an epoxy resin containing 20% ​​by mass of an amine curing agent.

[0032] According to the present invention, there is also provided a resin composition comprising the hydrophobic aluminum nitride powder.

[0033] In the above resin composition, it is preferred that

[0034] (1) The hydrophobic aluminum nitride powder is contained in an amount of 10 to 1500 parts by mass per 100 parts by mass of the resin.

[0035] (2) The aforementioned resin is an epoxy resin or a (meth)acrylic resin.

[0036] According to the present invention, further, a method for producing a hydrophobic aluminum nitride powder is provided, which comprises the following steps:

[0037] A step of preparing non-hydrophobic aluminum nitride powder as a raw material powder;

[0038] In the surface treatment step, the raw material powder is mixed with a silane compound, and the surface of the raw material powder is treated so that the hydrophobization degree is 1 to 45 and the carbon content derived from the silane compound is in the range of 0.1 to 0.5 mass %.

[0039] In the above production method, it is desirable that the molecular weight of the silane compound is 400 or less.

[0040] Effects of the Invention

[0041] The hydrophobic aluminum nitride powder of the present invention is a person formed by surface treatment using a silane compound as a hydrophobizing agent, and the hydrophobizing degree is in the range of 1 to 45 and the carbon content of the hydrophobizing agent (silane compound) introduced into the particle surface is in the range of 0.1 to 0.5 mass %. By so appropriately hydrophobizing, it is reflected that not only the hydrolyzability of the powder itself is greatly reduced, and the affinity with the resin is also improved, even in a resin composition (in a resin molded body) it is not easy to hydrolyze.

[0042] For example, as shown in the embodiments described later, if the hydrolysis property (basic hydrolysis rate in the resin) of the AlN powder in the epoxy resin molded body mixed with a specified amount of the hydrophobic aluminum nitride powder is measured, a value of less than 25% is shown (detailed measurement conditions refer to the embodiments). That is, the hydrophobic AlN powder of the present invention having the above-mentioned hydrophobicity and the carbon content derived from the hydrophobic agent is present on the particle surface in a constant ratio because the carbon derived from the hydrophobic agent is present on the particle surface, therefore, the affinity for the resin is greatly improved, and as a result, it will be closely fitted with the resin component in various resin molded bodies, and high hydrolysis resistance (water resistance) is also shown in the resin molded body. Moreover, surprisingly, if the reference hydrolysis rate in the resin measured under such conditions becomes less than 25%, when the composition of the molded body is different, for example, when a filler other than AlN powder is mixed, or when the resin is replaced with a resin other than epoxy resin (acrylic resin, etc.), low hydrolysis property is also shown. From this fact, it is inferred that the hydrophobic AlN powder of the present invention having the above-mentioned hydrophobization degree and carbon content has a high affinity for the polymer chain (substantially a hydrocarbon chain) forming the resin. That is, due to the high affinity with the polymer chain (hydrocarbon chain), even when the resin composition changes or the resin type is different, it exists in close contact with the resin component, and exhibits high hydrolysis resistance (water resistance) in the resin molded body.

[0043] Therefore, the hydrophobic aluminum nitride powder of the present invention is extremely useful as a filler to be blended in a resin composition for a heat dissipation material which is required to have high reliability under high humidity conditions. DETAILED DESCRIPTION

[0044] <Hydrophobic aluminum nitride powder>

[0045] The hydrophobic aluminum nitride powder of the present invention is composed of AlN particles that have been surface-treated with a silane compound. That is, the silane compound forms a chemical bond with a hydroxyl group or the like present on the surface of the aluminum nitride particles (or an oxide film formed on the surface) and bonds to other surfaces, thereby showing hydrophobicity and inhibiting the hydrolysis of aluminum nitride (AlN).

[0046] In the present invention, hydrophobicity is imparted by surface treatment with the silane compound, and the hydrophobization degree is in the range of 1-45, preferably 1-30.

[0047] The hydrophobicity is also called methanol wettability, which is a parameter measured by a method that hydrophobic aluminum nitride powder floats in water but completely suspends and settles in methanol. Specifically, 100cc of methanol aqueous solution with a methanol concentration difference of 1% by mass is placed in a beaker with a capacity of 200cc in advance. In each aqueous solution (beaker), 1g of AlN powder of the sample is added, and the aqueous solution in the beaker is stirred with a magnetic stirrer for 5 minutes. When 50% of the AlN powder is suspended and settled, the value of the volume percentage of methanol in the aqueous solution in the beaker is taken as the hydrophobicity. AlN powder with low hydrophobicity will not suspend and settle unless it is an aqueous solution with a high methanol concentration.

[0048] In the hydrophobic AlN powder of the present invention, it is also important that the carbon content derived from the silane compound (hydrophobizing agent) present on the particle surface is in the range of 0.1 to 0.5 mass %.

[0049] The carbon content is a value measured with a carbon analyzer after the hydrophobic treatment (after the surface treatment) and calculated according to the following formula.

[0050] Carbon content derived from silane compound (mass %) = A × 100 / B

[0051] A: Carbon content after hydrophobic treatment

[0052] B: Total mass of AlN powder after hydrophobic treatment

[0053] It should be noted that the carbon amount before the hydrophobic treatment can be substantially zero or can be an impurity level even if it is not zero, which is a negligible value. Therefore, the carbon amount before the hydrophobic treatment can be treated as zero, and the carbon amount relative to the gross mass of the AlN powder after the hydrophobic treatment can also be treated as the carbon content derived from the silane compound.

[0054] That is, when only the above-mentioned hydrophobicity is satisfied, the water resistance (hydrolysis resistance) as a powder is improved, but the water resistance in the resin is not satisfactory, and there are many aggregated particles, and the filling property of the resin is also low. Therefore, when the above-mentioned hydrophobicity is satisfied and the carbon content satisfies the above-mentioned range (0.1-0.5 mass%), not only the water resistance as a powder is high, but also the water resistance in the resin is improved, the aggregated particles are few, and the filling property of the resin is also high. For example, for a molded body formed by a resin composition compounded with the hydrophobic AlN powder, the hydrolysis resistance (water resistance in the resin) of the hydrophobic AlN powder to water penetrating into the molded body is very high.

[0055] For example, when an epoxy resin molded body (φ: 10 mm × 1.2 mm thick) containing 25% by mass of hydrophobic AlN powder is immersed in 50 g of ion exchange water for 90 hours, the decomposition rate (basic hydrolysis rate in the resin) of the AlN powder is extremely low, which is less than 25%. That is, the hydrophobic AlN powder of the present invention that meets the above-mentioned hydrophobicity and carbon content has hydrocarbon molecules of appropriate size distributed in appropriate amounts on the particle surface, so the affinity for the polymer chain forming the resin is greatly improved. As a result, the particles forming the AlN powder are closely attached to the resin, which can effectively inhibit the penetration of water, and the water resistance in the resin becomes extremely high. Therefore, as shown in the examples described later, when the compounding composition of the epoxy resin molded body is changed or the resin type is changed to an acrylic resin and the hydrolysis is measured in the same way, the same low decomposability is also shown.

[0056] Of course, the hydrophobic AlN powder of the present invention also has extremely low water resistance (hydrolysis resistance) as a powder.

[0057] In the present invention, the carbon content derived from the silane compound is roughly proportional to the density of the silane compound bonded to the particle surface. Therefore, the appropriate surface treatment amount using the silane compound can also be expressed according to the hydrophobic group density of the silane compound. For example, the hydrophobic group density of the hydrophobic group representing the number of silane compounds is suitable for the hydrophobic AlN powder of the present invention, which is 0.5 to 5.0 / nm. 2 , preferably between 1.0 and 4.0 per nm 2 The hydrophobic group density can be calculated from the above carbon content. In addition, it can also be calculated based on 29 Determined by SiNMR.

[0058] In the present invention, as the silane compound (hydrophobizing agent) satisfying the above-mentioned hydrophobizing degree and carbon content (hydrophobic group density), silane compounds with low hydrophobizing effect, such as those having a hydrocarbon group of appropriate size, can be used alone or in combination of two or more.

[0059] Among them, as described later, in terms of increasing the amount of surface hydroxyl groups by forming an oxide layer on the surface of the AlN powder, thereby increasing the reaction rate and increasing the silane compound density (Si density), silane compounds having a molecular weight of less than 400 or having an alkyl or alkylene group with a carbon number of less than 8 are particularly suitable.

[0060] For example, in the case of surface-treated AlN powders treated with silane compounds, part or all of the silane compounds are bonded to the surface of the particles due to a dehydration condensation reaction with the hydroxyl groups of the aluminum oxide layer present in a considerable amount on the surface of the AlN particles. The AlN powders treated with the surface are dispersed in an organic solvent, and even if solid-liquid separation is performed thereafter, a certain amount of silane is not washed away but remains in a powder state. The free silane compounds not bonded to the surface of the AlN particles are usually removed by washing with an organic solvent, heating under reduced pressure, etc.

[0061] Among the above-mentioned silane compounds, representative ones are silane compounds having a reactive functional group and silane compounds having no reactive functional group.

[0062] Examples of the silane compound having a reactive functional group include the following alkoxysilanes.

[0063] 3-Glycidoxypropyltrimethoxysilane,

[0064] 3-Glycidoxypropyltriethoxysilane,

[0065] 3-Glycidoxypropylmethyldimethoxysilane,

[0066] 3-Glycidoxypropylmethyldiethoxysilane,

[0067] 2-(3,4-Epoxycyclohexyl)ethyltrimethoxysilane,

[0068] 3-Methacryloyloxypropyltrimethoxysilane,

[0069] 3-Methacryloxypropyltriethoxysilane,

[0070] 3-methacryloxypropylmethyldimethoxysilane,

[0071] 3-methacryloxypropylmethyldiethoxysilane,

[0072] 3-Acryloxypropyltrimethoxysilane,

[0073] 3-Mercaptopropyltrimethoxysilane,

[0074] 3-Aminopropyltrimethoxysilane,

[0075] 3-Aminopropyltriethoxysilane,

[0076] 2-aminoethyl-3-aminopropyltrimethoxysilane,

[0077] 2-aminoethyl-3-aminopropylmethyldimethoxysilane,

[0078] 3-Dimethylaminopropyltrimethoxysilane,

[0079] 3-Diethylaminopropyltrimethoxysilane,

[0080] 3-Triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine,

[0081] N-phenyl-3-aminopropyltrimethoxysilane,

[0082] Vinyltrimethoxysilane,

[0083] Vinyltriethoxysilane,

[0084] p-V-phenyltrimethoxysilane,

[0085] Allyltrimethoxysilane;

[0086] Moreover, as a silane compound which does not have a reactive functional group, the following alkylalkoxysilane or arylalkoxysilane can be mentioned.

[0087] Methyltrimethoxysilane,

[0088] Dimethyldimethoxysilane,

[0089] Dimethyldiethoxysilane,

[0090] Trimethylmethoxysilane,

[0091] Ethyltrimethoxysilane,

[0092] n-propyltrimethoxysilane,

[0093] Isobutyltrimethoxysilane,

[0094] Isobutyltriethoxysilane,

[0095] n-Hexyltrimethoxysilane,

[0096] n-Hexyltriethoxysilane,

[0097] Cyclohexyltrimethoxysilane,

[0098] Cyclohexylmethyldimethoxysilane,

[0099] n-Octyltriethoxysilane,

[0100] Phenyltrimethoxysilane,

[0101] Phenyltriethoxysilane,

[0102] Diphenyldimethoxysilane,

[0103] Diphenyldiethoxysilane,

[0104] Trifluoropropyltrimethoxysilane,

[0105] Trifluoropropylmethyldimethoxysilane;

[0106] In addition to the above-mentioned alkoxysilanes, the following chlorosilane compounds can also be used.

[0107] Vinyltrichlorosilane,

[0108] Methyltrichlorosilane,

[0109] Dimethyldichlorosilane,

[0110] Trichloromethylsilane,

[0111] Ethyldimethylsilyl chloride,

[0112] Propyldimethylsilyl chloride,

[0113] Phenyltrichlorosilane,

[0114] Trifluoropropyltrichlorosilane,

[0115] Isopropyldiethylchlorosilane;

[0116] The hydrophobicity of the hydrophobic AlN powder of the present invention is relatively low, and the evaluation value of the water resistance of the epoxy resin used for the AlN powder with low hydrophobicity, i.e., the basic hydrolysis rate in the resin, shows an extremely low value, which is unpredictable by the existing hydrophobic technology. That is, the surface treatment of the AlN powder using a silane compound (hydrophobizing agent) is considered to reflect the degree of hydrophobization. The higher the hydrophobization degree, the higher the water resistance in the resin. However, for the water resistance of the AlN powder in the resin, the adhesion between the resin and the particles is dominant, and the surface treated AlN powder (with a high hydrophobization degree of more than 50) treated with the aforementioned silane compound with a strong hydrophobic group has a basic hydrolysis decomposition rate in the resin that is not necessarily low, but will exceed 25%.

[0117] The surface treated aluminum nitride powder of the present invention preferably has a particle size D of 50% of the cumulative volume in a particle size distribution measured by a laser diffraction scattering type particle size distribution analyzer using an ethanol solvent. 50 The hydrophobic AlN powder having such a small particle size has a large specific surface area when used as a filler, and forms a large interface with the resin, so the effect of the present invention is particularly significant.

[0118] In addition, the particle size D of the hydrophobic AlN powder of the present invention at 90% of the cumulative volume is 90 It is preferably 100 μm or less, and more preferably 20 μm or less.

[0119] Furthermore, the surface-treated aluminum nitride powder of the present invention preferably has a BET specific surface area A of 0.1 to 6.0 m2 as measured by a nitrogen adsorption single-point method. 2 / g range.

[0120] <Production of Hydrophobic AlN Powder>

[0121] The hydrophobic AlN powder of the present invention is produced, for example, through the following steps.

[0122] A step of preparing non-hydrophobic aluminum nitride powder as a raw material powder;

[0123] In a surface treatment step, the raw material powder is mixed with a silane compound to obtain a hydrophobicity of 1 to 45, particularly 1 to 30, and a carbon content derived from the silane compound of 0.1 to 0.5 mass % (or a hydrophobic group density derived from the silane compound of 0.5 to 5.0 pcs / nm). 2 , especially 1.0 to 4.0 / nm 2 ) to perform surface treatment on the raw material powder;

[0124] Raw powder:

[0125] As the raw material powder, non-hydrophobic AlN powder, i.e., AlN powder not subjected to surface treatment, AlN powder produced by a conventionally known method can be used without particular limitation, for example, AlN powder produced by direct nitridation, reduction nitridation, gas phase synthesis, etc.

[0126] In addition, it is unrelated to the size of particle size distribution and average particle diameter, and it is desired that the aggregate contained in the raw material powder is few. Aggregate directly remains in the hydrophobic AlN after surface treatment, which is easy to become the reason for the deterioration of the filling property of resin. In addition, the pores possessed by the aggregate also remain even after being filled into the resin molding, and are easily hydrolyzed due to the water immersed. And then, the aggregate is not easily surface-treated inside, so if the aggregate is broken after the surface treatment process, the untreated surface without surface treatment is exposed, and therefore, such untreated surface is easily hydrolyzed, and the compatibility with resin is also not good. Therefore, it is preferred that before the surface treatment process, it is broken with a ball mill, a jet mill, etc. as required, or dry classification and wet classification are utilized to remove from the raw material powder.

[0127] In addition, the particle size distribution of the raw non-hydrophobic AlN powder is not particularly limited and can be appropriately determined in consideration of the change in particle size of the target hydrophobic AlN powder caused by the surface treatment. For example, in the particle size distribution measured by a laser diffraction scattering type particle size distribution analyzer using an aqueous solvent, the particle size D 50 It is preferably within a range of 20 μm or less.

[0128] Furthermore, it is desirable that the specific surface area of ​​the raw material powder measured by the BET method is 0.6 m 2 / g or above.

[0129] It should be noted that in the above-mentioned non-hydrophobic AlN powder, about 5% by mass can be used as an upper limit to include impurities derived from the raw materials used in the synthesis of AlN or impurities such as alkaline earth elements and rare earth elements added during the synthesis process. In addition, as impurities derived from anti-aggregation agents and setters, boron nitride can also be included as an upper limit of about 5% by mass. However, the impurities that significantly reduce the crystallinity of AlN will become the cause of reduced thermal conductivity, so it is not preferred. The aluminum nitride content in the raw material powder is preferably more than 90% by mass, more preferably more than 95% by mass, and further preferably more than 99% by mass.

[0130] The hydrophobic AlN powder of the present invention is formed by bonding the silane compound as a hydrophobizing agent to the surface of the aluminum nitride particles at a high density. Therefore, the hydrophobic AlN powder as a raw material for surface treatment preferably has many oxide layers on the surface, but the oxide layer reduces the thermal conductivity of the AlN powder. Therefore, the oxide layer on the surface of the particle preferably stays at an amount that does not significantly reduce the thermal conductivity. For example, when the thickness of the oxide layer is about 0.005% to 0.2% of the diameter of the particle, the density of the hydroxyl group that can react with the silane compound in the oxide layer becomes 0.8 / nm 2 above.

[0131] The treatment for forming an oxide layer on the surface of the non-hydrophobic AlN powder particles as a raw material is preferably performed so that the density of the hydroxyl groups of the AlN powder becomes 0.8 to 2 / nm. 2 , especially 0.9 to 1.6 / nm 2 The above hydroxyl density is more than 2 / nm 2 The excessively oxidized particles are different from the surface of ordinary aluminum nitride, and there is a possibility that the oxidation reaction is excessively advanced, or the hydrolysis is advanced and degenerated into aluminum hydroxide. Such a state becomes a surface with low thermal conductivity, which is not preferable.

[0132] The formation of the oxide layer can be formed by natural oxidation during the storage of AlN powder (non-hydrophobic AlN powder), or by an intentional oxidation treatment process. In addition, the oxidation treatment of AlN powder can be carried out during the manufacture of aluminum nitride, or it can be carried out as a separate process after the manufacture of aluminum nitride. For example, for the non-hydrophobic AlN powder obtained by the reduction nitridation method, an oxidation treatment process is performed during the manufacture process for the purpose of removing the carbon used during the reaction, so that an aluminum oxide layer exists on the surface. For the aluminum nitride powder obtained by the reduction nitridation method, an oxidation treatment process can be further added.

[0133] When the additional oxidation treatment step is performed as a separate step, the suitable conditions are as follows. The non-hydrophobic AlN powder (raw material powder) obtained by various methods is heated in an oxygen-containing atmosphere, preferably at a temperature of 400 to 1000° C., more preferably at a temperature of 600 to 900° C., preferably for 10 to 600 minutes, more preferably for 30 to 300 minutes, so that an aluminum oxide layer can be formed on the surface of the AlN particles. As the above-mentioned oxygen-containing atmosphere, for example, oxygen, air, water vapor, carbon dioxide, etc. can be used, but in relation to the purpose of the present invention, it is preferred to treat in air, especially at atmospheric pressure.

[0134] On the other hand, when the oxidation treatment is carried out for a long time at a high temperature exceeding 1000°C, a thick oxide film may be formed on the surface of the AlN particles. The thermal expansion coefficient of the aluminum oxide film is different from that of the AlN core, so it is impossible to maintain a uniform film, and the film may break, and there is a concern that the AlN surface of the core may be exposed, which may cause a decrease in hydrolysis resistance. Therefore, it is best not to make the oxidation treatment conditions too harsh.

[0135] The shape of the primary particles of the non-hydrophobic AlN powder as the raw material powder in the present invention is not particularly limited, and can be any shape such as an indefinite shape, a spherical shape, a polyhedral shape, a columnar shape, a whisker shape, a flat plate shape, etc. Among them, in filler applications, a spherical shape with good viscosity characteristics and high reproducibility of thermal conductivity is desired. In addition, it is preferred that the particle aspect ratio is small. The suitable aspect ratio is 1 to 3.

[0136] Surface treatment process:

[0137] The raw material powder (non-hydrophobic AlN powder) is surface-treated with a silane compound, thereby obtaining the target hydrophobic AlN powder of the present invention.

[0138] As described above, the surface treatment is performed so that the hydrophobization degree is 1 to 45, particularly 1 to 30, and the carbon content derived from the silane compound is 0.1 to 0.5 mass % (or the density of the hydrophobic groups derived from the silane compound is 0.5 to 5.0 / nm). 2 , especially 1.0 to 4.0 / nm 2 ). Therefore, the amount of the silane compound varies depending on the type of the silane compound, the amount of OH groups present on the particle surface of the non-hydrophobic AlN powder to be surface treated, and the specific surface area of ​​the non-hydrophobic AlN powder, but is usually used in an amount of 0.1 to 5 parts by mass, preferably 0.2 to 1.0 parts by mass, relative to 100 parts by mass of the aluminum nitride powder having an oxide layer on the surface.

[0139] In the surface treatment with the silane compound, the silane compound is brought into contact with the non-hydrophobic AlN powder under heating, and then the free silane compound is removed as necessary.

[0140] The method of bringing the hydrophobic AlN powder into contact with the silane compound may be based on any method of dry surface treatment or wet surface treatment.

[0141] The dry surface treatment is a method based on dry mixing without using a large amount of solvent when mixing aluminum nitride powder with a hydrophobizing agent.

[0142] The dry mixing method includes the following methods.

[0143] A method of vaporizing a silane compound and mixing it with a raw material powder;

[0144] A method of spraying or dropping a liquid silane compound and mixing it with the raw material powder;

[0145] A method of diluting the silane compound with a small amount of an organic solvent to increase the amount of liquid, and further spraying or dropping the silane compound;

[0146] The method of gasification can be used to treat silane compounds with high volatility and low molecular weight. The method of diluting with an organic solvent is a method used when the amount of the silane compound is too small to be evenly dispersed in the entire powder. However, if too much organic solvent is used in the dilution, the liquid content of the entire powder becomes high, which becomes a cause of aggregation. When diluting, it is desired to dilute by about 5 to 50 times by weight. In any case, in the dry method, it is important to make the silane compound uniformly distributed throughout the entire raw material powder.

[0147] When mixing in a dry manner, it can be done while heating, or it can be done separately after fully mixing at room temperature. As for heating, it is desired to implement it as a method of firmly fixing the silane compound on the surface of the AlN particles. However, if heating is performed at too high a temperature, it is possible that the silane compound volatilizes, or the condensation of the silane compounds is excessively advanced, resulting in uneven treatment. In addition, if the mixing time at room temperature is set before starting heating, the silane compound will react throughout the whole, and it is easy to obtain a uniform treated powder. As the heating temperature during or after mixing, it is preferably 20 to 150°C, and particularly preferably about 40 to 130°C.

[0148] It should be noted that the silane compound may be subjected to surface treatment after being hydrolyzed with an acid or alkali in advance. However, the acid or alkali used in the hydrolysis, especially the alkaline substance, may deteriorate the surface of the AlN particles, and therefore, it is best to avoid using the acid or alkali used in the hydrolysis.

[0149] As dry mixing devices, general mixing and stirring devices such as planetary mixers, Henschel mixers, super mixers, V-type mixers, drum mixers, double cone mixers, and swing mixers can be used. It is desirable to give these devices a heating function. By heating while stirring, the process of surface treatment can be saved.

[0150] In addition, when dry mixing is used, powders tend to aggregate, so it is desirable to provide a mechanism such as a crushing blade or a shredder in the mixing device to dissolve the temporarily generated aggregates. During further mixing operations, the powders not only simply adhere, but sometimes, depending on the stirring mechanism, the powders may be pressed against the wall of the mixing container, thereby forming a thick adhesion layer, and thus, it becomes impossible to maintain the mixing state of the powders. Therefore, it is better if the wall of the mixing container is provided with anti-adhesion measures such as a fluororesin coating, a powder-dropping mechanism such as a shaker, and a scraping mechanism attached to the stirring blade.

[0151] In addition, the wet surface treatment is a method of using a solvent when mixing the aluminum nitride powder and the silane compound.

[0152] Compared with the dry method, the wet method can make the hydrophobizing agent uniformly spread over all particles, so that the treatment agent has less unevenness and the powder properties are stable. On the other hand, a drying step is required, and depending on the drying method, the silane compound may be segregated.

[0153] In such a wet method, a silane compound is added to a solvent, the raw material AlN powder is dispersed in the solvent, and heating, solvent removal, and heat drying are performed as necessary.

[0154] Here, the purpose of heating as needed is to promote the reaction between the silane compound and the surface of the AlN particles. The heating temperature is preferably about 50 to 120° C., and the time is preferably about 60 to 300 minutes. In addition, similar to the dry surface treatment, in order to fix the silane compound on the surface of the AlN particles, heating can also be performed after the solvent is removed. As the heating temperature, it is preferably about 20 to 150° C., and particularly preferably about 40 to 130° C.

[0155] Alternatively, heating may be performed under reduced pressure. By heating under reduced pressure, the excess hydrophobizing agent is removed, the treating agent does not become excessive, and aggregation of powders caused by the treatment can be prevented. The pressure during reduced pressure is preferably 10 hPa or less.

[0156] It should be noted that in the reaction between AlN powder and silane compound, the reactive groups of silane such as alkoxyl group need not all form bonds with aluminum nitride. However, the hydroxyl groups generated by the reaction of such reactive groups with water may sometimes cut the bond between the formed silane and AlN particles, so it is not preferred to add excess silane. Therefore, the amount of silane can be adjusted according to the amount of surface hydroxyl groups of aluminum nitride that reacts with silane.

[0157] In addition, the hydrophobic AlN powder obtained by the surface treatment may aggregate and the powder properties and the filling property into the resin may be impaired. In this case, it is preferable to remove the coarse particles by crushing or classifying.

[0158] The crushing and classification treatment is preferably carried out with a particle size D of 90% of the cumulative volume of the hydrophobic AlN powder. 90 The thickness is preferably 100 μm or less.

[0159] As a crushing method, dry crushing is preferred. In addition, a relatively gentle method that does not crush most of the aggregates that have been formed is desired. In particular, if strong crushing to the extent that even primary particles are destroyed is implemented using an apparatus or conditions, the effect of the present invention will be lost.

[0160] As the crushing device, dry crushing devices such as mortar type grinding machine, grinding mixer, chopper, hammer mill, pin mill, etc. can be cited. Among them, mortar type grinding machine which can selectively crush large aggregates in a short time and has less uneven crushing is preferred. The atmosphere of the crushing treatment is preferably in air or in an inert gas. In addition, the humidity of the atmosphere is preferably not too high, specifically, the humidity is less than 70%, more preferably less than 55%.

[0161] In addition, the classification process can be selected from either dry classification or wet classification, but when high-precision classification is not required, dry classification omitting the solvent removal step is desirable. As dry classification, airflow classification, vibrating sieve machine, etc. can be used.

[0162] The airflow classification method or device can be appropriately selected to obtain a particle size distribution suitable for the filler to be compounded into the resin. The airflow classification method is a method based on dispersing the powder in the airflow and using the gravity, inertia, centrifugal force, etc. of the particles at this time to separate into fine powder and coarse powder. In particular, the classification accuracy suitable for particles of several μm can be obtained by a classification device that uses inertia and centrifugal force.

[0163] As methods utilizing inertial force, for example, there are: a collision type that separates fine powder from coarse powder by setting guide blades inside the device to create a swirling flow of air, thereby bending the powder and granules riding the force of the airflow into a curve; a semi-free vortex centrifugal type that classifies particles by applying centrifugal force to the particles; and a wall-coanda type that utilizes the wall effect. As classification devices utilizing inertial force, there are cascade impactors, variable impactors, vortex airflow classifiers (aero fine classifiers), electrostatic air classifiers (eddy classifiers), elbow jets (elbow-jets), Hyper plex, etc.

[0164] The method using centrifugal force is to use vortex airflow to distinguish between fine powder and coarse powder. Therefore, as devices, free vortex type and forced vortex type can be cited. Free vortex type devices include: cyclone separators without guide blades, multi-stage cyclone separators, Turbo plex that uses secondary air and promotes the elimination of aggregation, dispersion separators that are equipped with guide blades to improve classification accuracy, Microspin, Microcut, etc. Forced vortex type devices use a rotating body inside the device to act on the particles with centrifugal force, and further create other air flows inside the device to improve the classification accuracy. Turboclassifier, DONASELEC, etc. can be cited.

[0165] It should be noted that the above-mentioned crushing treatment and classification treatment may be used in combination.

[0166] In the present invention, the hydrophobicity of the AlN powder is moderately improved by the surface treatment with the silane compound, which not only improves the water resistance of the powder itself, but also improves the adhesion between the resin and the AlN particles when mixed with the resin, so that the AlN particles in the resin molded body are less susceptible to hydrolysis.

[0167] <Resin composition>

[0168] When the hydrophobic AlN powder of the present invention is filled in a resin to form a resin composition, it exhibits excellent water resistance. The resin used in the composition of such a resin composition can be used without limitation, thermosetting resin or thermoplastic resin, but the hydrophobic AlN powder of the present invention is particularly effective for resins that have the property of water easily infiltrating into the resin matrix.

[0169] In the above resin composition, the hydrophobic AlN powder of the present invention can be used in a ratio of 10 to 1500 parts by mass relative to 100 parts by mass of the resin. 50In the case of a hydrophobic AlN powder having a particle size distribution of 0.5 to 20 μm, it is particularly preferred that the amount of the hydrophobic AlN powder be 10 to 700 parts by mass and the resin composition be composed in combination with other fillers.

[0170] In the present invention, examples of the thermosetting resin include phenol resins, epoxy resins, melamine resins, urea resins, unsaturated polyester resins, diallyl phthalate resins, polyurethane resins, silicone resins, and the like.

[0171] In addition, the following can be exemplified as the thermoplastic resin.

[0172] Vinyl polymer resins such as acrylic resin and polystyrene;

[0173] Polyamide;

[0174] nylon;

[0175] Polyacetal;

[0176] Polycarbonate;

[0177] Polyphenylene ether,

[0178] Polyesters such as polyethylene terephthalate;

[0179] Cyclic polyolefins;

[0180] Polyphenylene sulfide;

[0181] Polytetrafluoroethylene;

[0182] Polysulfone;

[0183] Liquid crystal polymers;

[0184] PEEK;

[0185] Thermoplastic Polyimide

[0186] Polyamide-imide;

[0187] Among them, epoxy resin and (meth) acrylic resin are preferred in consideration of compatibility with resins mainly used in common heat dissipation materials. In addition, they have the advantage of being easily cured by heating or light irradiation when using the manufacturing method described later. These resins can be used alone or in combination.

[0188] Hereinafter, epoxy resins and (meth)acrylic resins that are preferably used will be described.

[0189] <Epoxy resin>

[0190] The epoxy resin that can be used in the present invention is not particularly limited, and common epoxy resins can be used. Specific examples thereof are as follows.

[0191] Bisphenol A epoxy resin;

[0192] Bisphenol F epoxy resin;

[0193] Phenol novolac type epoxy resin;

[0194] Cresol novolac type epoxy resin;

[0195] Cycloaliphatic epoxy resin;

[0196] Heterocyclic epoxy resin;

[0197] Glycidyl ester type epoxy resin;

[0198] Glycidylamine type epoxy resin;

[0199] Biphenyl type epoxy resin;

[0200] Epoxy resin containing naphthalene ring;

[0201] Cyclopentadiene epoxy resin

[0202] Among the above, bisphenol A type epoxy resin, bisphenol F type epoxy resin, and biphenyl type epoxy resin are preferred.

[0203] As a curing agent for curing the epoxy resin, a substance generally used as a curing agent for epoxy resin can be used. As specific examples, the following substances can be exemplified.

[0204] Thermosetting curing agents, such as amines, polyamides, imidazoles, acid anhydrides, boron trifluoride-amine complexes, dicyandiamide, organic acid hydrazines, phenol novolac resins, bisphenol novolac resins, cresol novolac resins, etc.;

[0205] Photocuring agents, such as diphenyliodonium hexafluorophosphate, triphenylsulfonium hexafluorophosphate, etc.;

[0206] Among them, amines, imidazoles and acid anhydrides are preferred.

[0207] Specific examples of the amine curing agent include the following amine compounds.

[0208] Chain aliphatic amines, such as

[0209] Diethylenetriamine,

[0210] Triethylenetetramine,

[0211] Tetraethylenepentamine,

[0212] Dipropylenediamine,

[0213] Diethylaminopropylamine;

[0214] Cyclic aliphatic amines, such as

[0215] N-aminoethylpiperazine,

[0216] Isophoronediamine;

[0217] Cyclic aromatic polyamines, such as

[0218] m-Xylenediamine;

[0219] Aromatic amines, such as

[0220] Metaphenylenediamine,

[0221] Diaminodiphenylmethane,

[0222] Diaminodiphenyl sulfone;

[0223] Specific examples of the imidazole curing agent include the following imidazole compounds.

[0224] 2-Methylimidazole;

[0225] 2-ethyl-4-methylimidazole;

[0226] 1-Cyanoethyl-2-undecyl imidazole trimellitate;

[0227] Epoxyimidazole adducts;

[0228] Examples of the acid anhydride curing agent include the following acid anhydride compounds.

[0229] Phthalic anhydride;

[0230] Trimellitic anhydride;

[0231] Pyromellitic anhydride;

[0232] Benzophenone tetracarboxylic anhydride;

[0233] Ethylene glycol bis(trimellitate);

[0234] Maleic anhydride;

[0235] Tetrahydrophthalic anhydride;

[0236] Methyltetrahydrophthalic anhydride;

[0237] Methylendamethylenetetrahydrophthalic anhydride;

[0238] Methylbutenyltetrahydrophthalic anhydride;

[0239] Dodecenylsuccinic anhydride;

[0240] Hexahydrophthalic anhydride;

[0241] Succinic anhydride;

[0242] Methylcyclohexene dicarboxylic anhydride;

[0243] Alkylstyrene-maleic anhydride copolymer;

[0244] Chlorendic anhydride;

[0245] Polyazelaic anhydride;

[0246] In addition to the above-mentioned epoxy resin and curing agent, a curing accelerator may be blended as necessary to allow curing. Specific examples of the curing accelerator include the following compounds.

[0247] Imidazole curing accelerators, such as imidazole and 2-methylimidazole;

[0248] Phosphine derivatives, for example triphenylphosphine, tri-p-methoxyphenylphosphine, tricyclohexylphosphine;

[0249] Cyclic amidine derivatives, for example 1,8-diazabicyclo(5.4.0)undec-7-ene;

[0250] Furthermore, when the mixture of the epoxy resin, the curing agent and the curing accelerator is high in viscosity, a reactive diluent having an epoxy group may be further mixed. General substances may also be used as the reactive diluent. As specific examples of the reactive diluent, the following compounds may be exemplified.

[0251] n-Butyl glycidyl ether;

[0252] Allyl glycidyl ether;

[0253] Styrene oxide;

[0254] Phenyl glycidyl ether;

[0255] Glycidyl methacrylate;

[0256] p-Sec-butylphenyl glycidyl ether;

[0257] Diglycidyl ether;

[0258] (Poly)ethylene glycol diglycidyl ether;

[0259] (Poly)propylene glycol diglycidyl ether;

[0260] Butanediol diglycidyl ether;

[0261] Diglycidyl aniline;

[0262] Glyceryl triglycidyl ether;

[0263] <(Meth)acrylic resin>

[0264] The (meth)acrylic resin that can be used in the present invention is not particularly limited, and common (meth)acrylic resins can be used.

[0265] As examples of the monofunctional monomer used for forming the (meth)acrylic resin, the following compounds can be exemplified.

[0266] (Meth)acrylonitrile;

[0267] (Meth)acrylamide;

[0268] (Meth)acrylic acid;

[0269] Methyl (meth)acrylate;

[0270] Ethyl (meth)acrylate;

[0271] Hydroxyethyl (meth)acrylate;

[0272] Butyl (meth)acrylate;

[0273] Hydroxybutyl (meth)acrylate;

[0274] 2-(Meth)acryloyloxyethyl succinate;

[0275] 2-(Meth)acryloyloxyethyl maleate and its salts;

[0276] 2-(Meth)acryloyloxyethyl phthalate;

[0277] Trifluoroethyl (meth)acrylate;

[0278] Perfluorobutyl ethyl (meth)acrylate;

[0279] Perfluorooctyl ethyl (meth)acrylate;

[0280] Dimethylaminoethyl (meth)acrylate;

[0281] Diethylaminoethyl (meth)acrylate;

[0282] (Meth)acryloyloxyethyl hydrogen phosphate;

[0283] As examples of the polyfunctional monomer used for forming the (meth)acrylic resin, the following compounds can be exemplified.

[0284] Ethylene glycol di(meth)acrylate;

[0285] Propylene glycol di(meth)acrylate;

[0286] 1,4-Butanediol di(meth)acrylate;

[0287] 1,6-Hexanediol di(meth)acrylate;

[0288] 1,9-nonanediol di(meth)acrylate;

[0289] 1,10-Decanediol di(meth)acrylate;

[0290] Glyceryl di(meth)acrylate;

[0291] Tetrafluoroethyl di(meth)acrylate;

[0292] Hexafluoropropyl di(meth)acrylate;

[0293] Octafluorobutyl di(meth)acrylate;

[0294] Bis[2-(meth)acryloyloxyethyl] hydrogen phosphate,

[0295] Bisphenol A di(meth)acrylate of ethylene oxide adduct or propylene oxide adduct; bisphenol A-diepoxy-acrylic acid adduct;

[0296] Tricyclodecane dimethanol diacrylate;

[0297] Urethane di(meth)acrylate;

[0298] Pentaerythritol tri(meth)acrylate;

[0299] The above-mentioned multifunctional monomer may be used alone to form a (meth)acrylic resin, or may be mixed with a monofunctional monomer to form a (meth)acrylic resin.

[0300] In order to polymerize and cure the (meth)acrylic monomer, a thermal radical polymerization initiator may be used.

[0301] As examples of the thermal radical polymerization initiator, the following compounds can be exemplified.

[0302] Organic peroxides, such as

[0303] Caprylyl peroxide,

[0304] Lauroyl peroxide,

[0305] Tert-butyl peroxy-2-ethylhexanoate,

[0306] Benzoyl peroxide,

[0307] Tert-butyl peroxyisobutyrate,

[0308] Tert-butyl peroxylaurate,

[0309] Tert-Hyl Perbenzoate,

[0310] Di-tert-butyl peroxide;

[0311] Azo bi-system polymerization initiators, such as

[0312] 2,2-azobisisobutyronitrile,

[0313] 2,2-Azobis-(2,4-dimethylvaleronitrile);

[0314] Among the above-mentioned polymerization initiators, when the polymerization is carried out at 80° C. to 160° C., benzoyl peroxide, t-butyl peroxy-2-ethylhexanoate, and the like can be preferably used.

[0315] These polymerization initiators are usually used in an amount of 0.1 to 20 parts by mass, preferably 0.5 to 10 parts by mass, based on 100 parts by mass of the monomer.

[0316] When photocuring is used as the curing reaction, a known initiator can be used as the (meth)acryloyl photopolymerization initiator.

[0317] When the hydrophobic AlN powder of the present invention is used as a filler, other fillers may be included. The filler is not necessarily a thermally conductive filler, and may be combined with a filler having low thermal conductivity when improvement in filling properties is expected.

[0318] The combination with the above-mentioned other fillers is useful for improving the filling property when the particle size of the hydrophobic AlN powder is small. 50 The above-mentioned 0.5 to 8 μm embodiment is particularly suitable for using a hydrophobic AlN powder with a small particle size. In this case, as the particle size of other fillers, D 50 The appropriate diameter is 15 to 100 μm, and the other filler is preferably used in an amount of 150 to 900 parts by mass relative to 100 parts by mass of the hydrophobic AlN powder. The other filler will be described later, but among them, alumina is preferred.

[0319] Examples of the thermally conductive filler include alumina, boron nitride, ZnO, MgO, carbon fibers, and diamond particles.

[0320] In addition, composite oxides such as silica, quartz, talc, mica, silica-titania, silica-zirconium oxide, silica-barium oxide, silica-aluminum, silica-calcium oxide, silica-strontium oxide, and silica-magnesium oxide, and silicates such as zeolite and montmorillonite can also be used as thermally conductive fillers.

[0321] In addition, the filler may or may not be surface treated. When other surface treated fillers are used, it is preferred in terms of filling properties to use a filler having the same or similar properties as the silane compound used in the hydrophobic AlN powder of the present invention.

[0322] When forming a resin molded body, in addition to fillers and resin raw materials, known additives may be contained. The purpose of adding additives may include improving the filling property of the filler and improving the mechanical properties of the resin molded body.

[0323] Such additives can be used without particular limitation as long as they do not hinder the adhesion between the hydrophobic AlN powder and the resin and do not hinder the thermal conductivity. However, the use of additives that promote the hydrolysis of aluminum nitride and those that react with aluminum nitride to generate different compounds should be avoided. In addition, organic solvents can be used as long as they are removed during the process of forming the final resin molded body.

[0324] As the additive, a silane compound can be particularly preferably used from the viewpoint of affinity with hydrophobic AlN and other general fillers.

[0325] The silane compound is preferably blended in a ratio of 0.01 to 5 parts by mass based on 100 parts by mass of the resin.

[0326] Specific examples of the silane compound used as the additive are as follows.

[0327] Epoxy-containing silanes, such as

[0328] 3-Glycidoxypropyltrimethoxysilane,

[0329] 3-Glycidoxypropyltriethoxysilane,

[0330] 3-Glycidoxypropylmethyldimethoxysilane,

[0331] 3-Glycidoxypropylmethyldiethoxysilane,

[0332] 2-(3,4-Epoxycyclohexyl)ethyltrimethoxysilane;

[0333] Methacryl-containing silanes, such as

[0334] 3-Methacryloyloxypropyltrimethoxysilane,

[0335] 3-Acryloxypropyltrimethoxysilane,

[0336] 3-Methacryloxypropyltriethoxysilane,

[0337] 3-methacryloxypropylmethyldimethoxysilane,

[0338] 3-Methacryloxypropylmethyldiethoxysilane;

[0339] Amino-containing silanes, such as

[0340] 3-Aminopropyltrimethoxysilane,

[0341] 3-Aminopropyltriethoxysilane,

[0342] 2-aminoethyl-3-aminopropyltrimethoxysilane,

[0343] 3-Triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, 2-aminoethyl-3-aminopropylmethyldimethoxysilane,

[0344] 3-Dimethylaminopropyltrimethoxysilane,

[0345] 3-Diethylaminopropyltrimethoxysilane,

[0346] N-phenyl-3-aminopropyltrimethoxysilane;

[0347] Alkylsilanes, such as methyltrimethoxysilane,

[0348] Dimethyldimethoxysilane,

[0349] Dimethyldiethoxysilane,

[0350] Trimethylmethoxysilane,

[0351] Ethyltrimethoxysilane,

[0352] n-propyltrimethoxysilane,

[0353] Isobutyltrimethoxysilane,

[0354] Isobutyltriethoxysilane,

[0355] n-Hexyltrimethoxysilane,

[0356] n-Hexyltriethoxysilane,

[0357] Cyclohexyltrimethoxysilane,

[0358] Cyclohexylmethyldimethoxysilane,

[0359] n-Octyltriethoxysilane,

[0360] n-Decyltriethoxysilane,

[0361] Hexadecyltriethoxysilane,

[0362] n-Octadecyltriethoxysilane;

[0363] Fluorinated alkylsilanes, such as

[0364] Trifluoropropyltrimethoxysilane,

[0365] Trifluoropropylmethyldimethoxysilane;

[0366] Silanes containing aromatic groups, such as

[0367] Phenyltrimethoxysilane,

[0368] Phenyltriethoxysilane,

[0369] Diphenyldimethoxysilane,

[0370] Diphenyldiethoxysilane;

[0371] Mercapto-containing silanes, such as

[0372] 3-Mercaptopropyltrimethoxysilane,

[0373] 3-Mercaptopropylmethyldimethoxysilane;

[0374] Vinyl-containing silanes, such as

[0375] Vinyltrimethoxysilane,

[0376] Vinyltriethoxysilane;

[0377] Other silane compounds, such as

[0378] p-V-phenyltrimethoxysilane,

[0379] Allyltrimethoxysilane,

[0380] Tris-(trimethoxysilylpropyl)isocyanurate,

[0381] 3-isocyanatepropyltriethoxysilane,

[0382] 3-Ureidopropyltriethoxysilane;

[0383] The resin composition composed of the hydrophobic AlN powder of the present invention and a resin can be suitably used as a heat dissipating resin material.

[0384] As the use of the heat dissipation resin material manufactured using the hydrophobic AlN powder of the present invention, for example, materials for heat dissipation components for efficiently dissipating heat from semiconductor components carried by home appliances, automobiles, notebook personal computers, etc. can be cited. As specific examples thereof, for example, heat dissipation grease, heat dissipation gel, heat sink, phase change sheet, adhesive, etc. can be cited. In addition to these, the above-mentioned composite material can also be used as an insulating layer, semiconductor sealing agent, bottom filling glue, housing, heat dissipation fins, etc. used in, for example, metal base substrates, printed circuit boards, flexible substrates, etc.

[0385] Example

[0386] Hereinafter, the present invention will be described in more detail based on Examples, but the present invention is not limited to these Examples.

[0387] The raw materials used and the conditions for measuring physical properties are described below.

[0388] [Raw material AlN powder]

[0389] A1: H No. 1 grade powder produced by Tokuyama Corporation using a reduction nitridation method.

[0390] ·D 50 =1.20μm

[0391] ·Specific surface area 2.60m 2 / g

[0392] Oxygen concentration: 0.8 mass%

[0393] ·Surface hydroxyl number: 1.4 / nm 2

[0394] A2: HF-05 grade powder produced by Tokuyama Corporation using a reduction nitridation method.

[0395] ·D 50 =4.95μm

[0396] Surface area: 0.80m 2 / g

[0397] Oxygen concentration: 0.8 mass%

[0398] ·Surface hydroxyl number: 1.3 / nm 2

[0399] A3: AlN powder produced by direct nitridation.

[0400] ·D 50 =1.18μm

[0401] ·Specific surface area 2.72m 2 / g

[0402] Oxygen concentration 0.5 mass%

[0403] ·Surface hydroxyl number 0.3 / nm 2

[0404] [Alumina]

[0405] As an alumina filler used in combination with the AlN powder, A20s (average particle size: 22.7 μm) manufactured by Showa Denko was used.

[0406] [Hydrophobic agent]

[0407] ·MMS: Methyltrimethoxysilane (Tokyo Chemical Industry, >98%)

[0408] DMDS: dimethyldimethoxysilane (Tokyo Chemical Industry, >98%)

[0409] PRMS: Propyltrimethoxysilane (Tokyo Chemical Industry, >98%)

[0410] ·HES: Hexyltriethoxysilane (Tokyo Chemical Industry, >98%)

[0411] OES: Octyltriethoxysilane (Tokyo Chemical Industry, >97%)

[0412] GPS: 3-glycidoxypropyltrimethoxysilane (Tokyo Chemical Industry, >97%)

[0413] ·GOS: 8-glycidoxyoctyltrimethoxysilane (Shin-Etsu Chemical, >99%)

[0414] ECHS: 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane (Tokyo Chemical Industry, >97%)

[0415] MPS: 3-methacryloxypropyltrimethoxysilane (Tokyo Chemical Industry, >98%)

[0416] MOS: 8-methacryloyloxyoctyltrimethoxysilane (Shin-Etsu Chemical, >99%)

[0417] ·VMS: Vinyltrimethoxysilane (Tokyo Chemical Industry, >98%)

[0418] ·PMS: Phenyltrimethoxysilane (Tokyo Chemical Industry, >98%)

[0419] PAPS: N-phenyl-3-aminopropyltrimethoxysilane (Shin-Etsu Chemical, >95%)

[0420] ·AMS: 3-aminopropyltrimethoxysilane (Tokyo Chemical Industry, >97%)

[0421] ·AEPS: 2-aminoethyl-3-aminopropyltrimethoxysilane (Tokyo Chemical Industry, >97%)

[0422] AEOS: N-2-(aminoethyl)-8-aminooctyltrimethoxysilane (Shin-Etsu Chemical, >95%)

[0423] ·DMS: Decyltrimethoxysilane (Fujifilm Wako Pure Chemical Industries, Ltd., >98%)

[0424] [Epoxy resin]

[0425] ·Epoxy resin jER828 (Mitsubishi Chemical)

[0426] ·Amine curing agent jER CureW (Mitsubishi Chemical)

[0427] [Methacrylic resin]

[0428] BPE-100: Ethoxylated bisphenol A dimethacrylate (manufactured by Shin-Nakamura Chemical)

[0429] 3G: Triethylene glycol dimethacrylate (Fujifilm Wako Pure Chemical Industries, Ltd.)

[0430] [Curing catalyst for methacrylic resin]

[0431] ·Perbutyl O: tert-butyl peroxy-2-ethylhexanoate (made by NOF)

[0432] [Specific surface area]

[0433] The BET specific surface area of ​​the organic-inorganic composite particle powder was determined using a specific surface area measuring device (Flowsorb 2-2300 manufactured by Shimadzu Corporation) according to the BET method (nitrogen adsorption single-point method). 2 g of the organic-inorganic composite particle powder was used for the measurement, and the powder was dried in nitrogen flow at 100° C. for 1 hour.

[0434] [Particle size distribution]

[0435] Water was used as the solvent for the raw material AlN. Ethanol was used as the solvent for the hydrophobic AlN. AlN powder was dispersed in a solvent at a concentration of 0.2 mass %, and irradiated with ultrasonic waves of about 200W for 2 minutes to disperse it. The obtained liquid was measured for particle size distribution using a laser diffraction scattering particle size distribution analyzer. In the volume frequency distribution of particle size, the volume frequency was accumulated from the particle with the smallest particle size, and the value of the particle size when the cumulative value reached 50% was recorded as D 50 The value of the particle size when it reaches 90% is recorded as D90 In addition, in the present invention, D 50 The value is taken as the average particle size.

[0436] [Carbon analysis, hydrophobic group density]

[0437] The carbon content of the hydrophobic AlN powder is measured with a carbon analysis device (e.g., EMIA-110 manufactured by Horiba). The powder is burned at 1350 ° C in an oxygen stream until carbon dioxide gas is no longer produced, and the carbon content of each powder is quantified from the amount of carbon dioxide produced. The carbon content of the hydrophobic treatment layer from the hydrophobic AlN powder is calculated using the formula for calculating the carbon content from the silane compound disclosed herein. In addition, the hydrophobic group density is calculated based on the above carbon content.

[0438] [Surface hydroxyl content]

[0439] The amount of trimethylsilyl groups generated on the AlN surface when AlN powder was dry-treated with hexamethyldisilazane was measured by carbon analysis, and the amount of surface hydroxyl groups was calculated based on the amount.

[0440] [Oxygen concentration of AlN powder]

[0441] The oxygen concentration of the AlN powder was measured using an oxygen analyzer manufactured by Horiba, Ltd.

[0442] It was confirmed that at least 70% or more of the oxygen in the AlN particles was present in the surface oxide layer.

[0443] [Decomposition rate of AlN powder (water resistance)]

[0444] The water resistance of the raw AlN powder or the hydrophobic AlN powder was evaluated as follows. 3 1 g of sample powder and 50 g of ion exchange water were placed in a fluororesin container and stored at 25°C in a sealed container for 24 hours. The container was opened and the amount of ammonium ions in the collected water was quantified by ion chromatography. Assuming that AlN was hydrolyzed according to formula (1), the decomposition rate of AlN was calculated from the amount of ammonium ions.

[0445] AlN+3H2O→Al(OH)3+NH3 (1)

[0446] [Basic hydrolysis rate within the resin (water resistance)]

[0447] For the resin composition filled with raw material AlN powder or hydrophobic AlN powder as sample AlN powder, the water resistance test is implemented as follows. In the aforementioned epoxy resin to which the aforementioned curing agent is added at 20% by mass, the sample AlN powder is added in a proportion of 25% by mass, and it is kneaded in a mortar for 15 minutes. The above-mentioned kneaded product is hot-pressed at 150°C and 20MPa for 1 hour, and then heated at 180°C for 1 hour to cure it, and a disc-shaped cured body formed by the resin composition with a diameter of 10mm and a thickness of 1.2mm is obtained.

[0448] The obtained sample (solidified body) and 50 cc of ion exchange water were placed in a 50 cc fluororesin container with a lid. After being kept at 120°C for 90 hours, the container was cooled to 10°C and then opened. The amount of ammonium ions in the collected water was quantified by ion chromatography. Assuming that AlN was hydrolyzed according to formula (1), the basic hydrolysis rate in the resin was calculated from the measured value of the ammonium ions.

[0449] [Water resistance test of resin composition]

[0450] A resin composition was prepared according to the following method, and the decomposition rate (water resistance) was measured according to the above-mentioned method for measuring the basic hydrolysis rate (water resistance) in the resin.

[0451] <Epoxy resin composition>

[0452] The following raw materials were weighed and kneaded in a mortar for 15 minutes to obtain a kneaded product.

[0453] · Hydrophobic AlN powder 0.47g,

[0454] Alumina powder A20s 1.33g,

[0455] ·Epoxy resin jER828 0.12g,

[0456] Curing agent CureW 0.03g

[0457] The obtained kneaded product was subjected to hot press molding at 150° C. and 20 MPa for 1 hour, and was further heated at 180° C. for 1 hour to obtain a disk-shaped cured product of the resin composition having a diameter of 10 mm and a thickness of 1.2 mm.

[0458] <Acrylic resin composition>

[0459] The following raw materials were weighed and kneaded in a mortar for 15 minutes to obtain a kneaded product.

[0460] ·Hydrophobic AlN powder 0.47g

[0461] Alumina powder A20s 1.33g

[0462] ·Methacrylate monomer BPE-100 0.105g

[0463] 3G 0.045g

[0464] ·Perbutyl O 0.001g

[0465] The obtained kneaded product was subjected to hot press molding at 150° C. and 20 MPa for 3 hours to obtain a disk-shaped cured product composed of the resin composition having a diameter of 10 mm and a thickness of 1.2 mm.

[0466] Examples 1 to 22, Comparative Examples 1 to 7;

[0467] The hydrophobic AlN powder was obtained by the method described in the following production example (see Table 1). The D 50 , carbon content, hydrophobic group density, specific surface area, hydrophobization degree, powder decomposition rate, and basic hydrolysis rate in resin. In addition, hydrophobic AlN powder was used to manufacture the aforementioned epoxy resin composition and acrylic resin composition, and the water resistance test was performed. The results are summarized in Tables 2 and 3.

[0468] <Manufacturing Example>

[0469] 600 g of the raw aluminum nitride powder shown in Table 1, 2.45 g of the hydrophobizing agent shown in Table 1 corresponding to 30 mmol / g, and 1200 g of isopropyl alcohol were placed in a glass eggplant-shaped bottle and stirred for 30 minutes using a fluororesin stirring blade. After isopropyl alcohol was removed under reduced pressure at 50° C. in a rotary evaporator, the mixture was dried under reduced pressure at 100° C. to obtain a hydrophobic aluminum nitride powder.

[0470] Comparative Example 8;

[0471] The hydrophobicity, decomposition rate of the powder, and basic hydrolysis rate in the resin of the AlN powder A1 without surface treatment were measured. In addition, the aforementioned epoxy resin composition and acrylic resin composition were prepared using the hydrophobic AlN powder and subjected to water resistance tests. The results are summarized in Tables 2 and 3.

[0472] [Table 1]

[0473]

[0474] [Table 2]

[0475]

[0476] [Table 3]

[0477]

Claims

1. A hydrophobic aluminum nitride powder, characterized in that: It is a hydrophobic aluminum nitride powder with a hydrophobization degree of 1 to 45. The carbon content derived from the hydrophobizing agent is in the range of 0.1 to 0.5 mass %, and the hydrophobizing agent is an alkoxysilane.

2. The hydrophobic aluminum nitride powder according to claim 1, wherein The molecular weight of the alkoxysilane is 400 or less. 3 . The hydrophobic aluminum nitride powder according to claim 1 , wherein the hydrophobicity degree of the powder is in the range of 1 to 30.

4. The hydrophobic aluminum nitride powder according to claim 1, wherein In the particle size distribution measured by a laser diffraction scattering type particle size distribution analyzer using an ethanol solvent, the particle size D at which the cumulative volume is 50% is 50 0.5~20μm.

5. The hydrophobic aluminum nitride powder according to claim 1, wherein The decomposition rate of the aluminum nitride measured after immersing the following test body in 50 g of ion exchange water at 120° C. for 90 hours was 25% or less. The test body is a 10 mm φ×1.2 mm thick molded body formed from a resin composition obtained by blending 25 parts by mass of a hydrophobic aluminum nitride powder with respect to 100 parts by mass of an epoxy resin containing 20% ​​by mass of an amine curing agent. A resin composition comprising the hydrophobic aluminum nitride powder according to claim 1 .

7. The resin composition according to claim 6, wherein The hydrophobic aluminum nitride powder is contained in an amount of 10 to 1500 parts by mass per 100 parts by mass of the resin.

8. The resin composition according to claim 7, wherein The resin is epoxy resin or (meth) acrylic resin.

9. A method for producing hydrophobic aluminum nitride powder, comprising the following steps: A step of preparing a non-hydrophobic aluminum nitride powder as a raw material powder; and, In the surface treatment step, the raw material powder is mixed with a silane compound, and the surface of the raw material powder is treated so that the hydrophobization degree is 1 to 45 and the carbon content derived from the alkoxysilane is in the range of 0.1 to 0.5 mass %.

10. The method for producing a hydrophobic aluminum nitride powder according to claim 9, wherein: The molecular weight of the alkoxysilane is 400 or less.

Citation Information

Patent Citations

  • Ceramic powder having modified surface

    JP1985123561A

  • Water-resistant aluminum nitride powder

    JP1997202608A

  • Aluminum nitride powder

    JP2000129160A

  • Aluminum nitride powder

    JP2004083334A

  • Aluminum nitride powder and its producing method

    JP2005104765A